Instrumentation for the Citizen CATE Experiment: Faroe Islands and Indonesia. (12th December 2016) - Penn, M J; Baer, R; Bosh, R; Garrison, D; Gelderman, R; Hare, H; Isberner, F; Jensen, L; Kovac, S; McKay, M; Mitchell, A; Pierce, M; et al.
Abstract: The inner regions of the solar corona from 1–2.5 Rsun are poorly sampled both from the ground and space telescopes. A solar eclipse reduces the sky scattered background intensity by a factor of about 10, 000 and opens a window to view this region directly. The goal of the Citizen Continental-America Telescopic Eclipse (CATE) Experiment is to take a 90-minute time sequence of calibrated white-light images of this coronal region using 60 identical telescopes spread from Oregon to South Carolina during the 2017 August 21 total solar eclipse. Observations that can address questions of coronal dynamics in this region can be collected with rather modest telescope equipment, but the large dynamic range of the coronal brightness requires careful camera control. The instruments used for test runs on the Faroe Islands in 2015 and at five sites in Indonesia in 2016 are described. Intensity calibration of the coronal images is done and compared with previous eclipse measurements from November & Koutchmy and Bazin et al. The change of coronal brightness with distance from the Sun seen in the 2016 eclipse agrees with observations from the 1991 eclipse, but differ substantially from the 2010 eclipse. The 2015 observations agree with 2016 and 1991 solar radii near the Sun, but are fainter at larger distances. Problems encountered during these test runs are discussed as well the solutions which will be implemented for the 2017 eclipse experiment.